PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING PADA MATERI KPK DAN FPB DI KELAS V SD - Dini Ayu Ningsih; Hidayat, Hidayat (Bajang Institute, 2024)
This study aims to design problem-based learning worksheets on KPK and FPB material that are suitable for use in the learning process in grade V SD. This study uses the ADDIE development procedure which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. However, in this study the ADDIE procedure was used only up to stage 4, namely Implementation. Data collection techniques carried out in this study, namely observation, questionnaires, interviews and documentation. From the results of the validation carried out on several expert validators, a percentage of 88% was obtained from the results of the material expert validation in the